analyzing the effectivenes of boarding school managemen in shaing religious characterat MA Mu'allimin NW Anjani - dedi efendy (Innovative Pedagogy and Education Studies, 2024)
This study aims to analyze the effectiveness of boarding school management in shaping students’ religious character at MA Mu’allimin NW Anjani. Boarding school management plays a strategic role in organizing educational activities, discipline, religious programs, and daily supervision that contribute to students’ moral and spiritual development. This research employs a qualitative descriptive approach, with data collected through observations, interviews, and documentation involving school leaders, teachers, dormitory supervisors, and students. The results show that the effectiveness of boarding school management is reflected in well-structured religious programs, consistent implementation of rules, exemplary behavior from educators, and a supportive boarding environment. These factors significantly influence the formation of students’ religious character, including discipline in worship, moral behavior, responsibility, and social awareness. However, several challenges remain, such as limited facilities and differences in students’ backgrounds, which affect the optimal implementation of management programs. Overall, effective boarding school management contributes positively to shaping students’ religious character at MA Mu’allimin NW Anjani.